1985
DOI: 10.1002/jsfa.2740360711
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and some properties of the lipase present in oil palm (Elaeis guineensis) mesocarp

Abstract: The fatty layer obtained by centrifuging a homogenate of oil palm fruit mesocarp contains an active lipase. The lipase which was partially purified using a combination of ammonium sulphate fractionation, ion exchange and gel filtration chromatography, indicated an optimum activity at pH 4.5 and a temperature of 30°C. The enzyme exhibited good activity towards its natural substrate, palm oil as well as glycerol trioleate and glycerol tripalmitate. It also showed a linear reaction rate for the first 20 min of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
8

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 10 publications
2
25
0
8
Order By: Relevance
“…Similarly, the consumption of RPOL in virgin form is being prevented by the high free fatty acid content. Free fatty acids (FFA) are produced naturally in crude palm oil (CPO) and this gets increased by the action of powerful hydrolytic enzymes present on the exterior of the palm fruit and by microbial lipases most probably originating from yeast cells; and hydrolysis of oil during poor and lengthy storage (Abigor et al 1985;Tan et al 2009). Prasanth Kumar and Gopala Krishna (2014b) made an attempt to retain palm phytonutrients by enzymatic esterification of free fatty acids with added glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the consumption of RPOL in virgin form is being prevented by the high free fatty acid content. Free fatty acids (FFA) are produced naturally in crude palm oil (CPO) and this gets increased by the action of powerful hydrolytic enzymes present on the exterior of the palm fruit and by microbial lipases most probably originating from yeast cells; and hydrolysis of oil during poor and lengthy storage (Abigor et al 1985;Tan et al 2009). Prasanth Kumar and Gopala Krishna (2014b) made an attempt to retain palm phytonutrients by enzymatic esterification of free fatty acids with added glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…A optimum temperature of 45 o C has previously been reported for lipases from some seeds of Jatropha curcas L. (Abigor et al, 2002). Abigor et al (1985) purified oil palm lipase which had optimum temperature of 30°C, above which there was a steady decline. Enujiugha et al, 2004 observed a gradual decline in the activity of the lipase from conophor nut with successive increases in temperature, from 30-80°C.…”
Section: Discussionmentioning
confidence: 86%
“…A pH optimum from 7.5 has previously been reported for lipases from some seeds of Jatropha curcas L. (Abigor et al, 1985). However, lipase from Cucumeropsis manii showed pH optima at 4.5 and 7.5 suggesting the presence of both acidic and alkaline lipases (Eze and Chilaka, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…This could have resulted from lipolytic activities of exogenous microorganisms which have been shown to commonly infect over-ripe loose fruits (Coursey and Eggins 1961 ;Esechie 1978). The high level of FFA recorded in the over-ripe fruh mesocarp lipid may also be a result of lipase enzyme adtivity (Abigor et al 1985). Table 2 indicates that the most important biosynthetic activity occurring in the developing oil palm fruit mesocarp is the synthesis of TG.…”
Section: Resultsmentioning
confidence: 99%